Analisis Penghuni dan Adaptasi Ruang dari Persfektif Behavioral Architecture di Perumahan Trieng Dua Peurde Kota Lhokseumawe - Rizka Aulan Nisa; Soraya Masthura Hassan; Dela Andriani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
A good home is one that considers the basic aspects of the needs of the occupants. The incompatibility of the initial space in accommodating human behavior often occurs in the construction of mass houses that only attach importance to profit, the speed of development to pursue targets so that it does not consider aspects of resident behavior.  The purpose of the study is to understand and analyze how resident behavior can result in adaptations to spaces in mass housing. This research uses a qualitative, descriptive approach method. The research sample was selected using purposive sampling. The analysis showed that the average sample of residential units experienced spatial adaptation by adjusment and by reaction. The adaptation by wihtdrawal was only found in one house unit.